Increased Peptide YY blood concentrations, not decreased acyl-ghrelin, are associated with reduced hunger and food intake in healthy older women: preliminary evidence - Hickson,M; Frost,G; Dhillo,WS; Moss,C; Bottin,J (Appetite, 2016)
With ageing there is frequently a loss of appetite, termed anorexia of ageing, which can result in under-nutrition. We do not know how appetite control alters with ageing. The objective of this study was to investigate whether differences in the release of, and response to, gastrointestinal appetite hormones is altered in young compared to old healthy volunteers. We hypothesised that an increase in PYY and GLP-1 or a decrease ghrelin may result in a decreased appetite. A comparative experimental design, using a cross-sectional sample of ages from a healthy population, matched for sex and BMI was used. The study compared total ghrelin, acyl-ghrelin, PYY, GLP-1 and subjective appetite responses to ingestion of a standardised 2781kj (660kcal) test meal. 31 female volunteers aged between 21-92yrs took part. Multiple linear regression showed that both age and sex had an independent effect on energy intake. Subjective appetite scores showed that hunger, pleasantness to eat, and prospective food intake were significantly lower in the older age groups. PYY incremental area under the curve (IAUC) was greater in the oldest old compared to younger ages f(3,27)=2.9, p=0.05. No differences in GLP-1, ghrelin or acyl-ghrelin were observed in the older compared to younger age groups. Our data suggest that there may be increases in postprandial PYY(3-36) levels in female octogenarians, potentially resulting in reduced appetite. There does not appear to be any change in ghrelin or acyl-ghrelin concentrations with ageing.